2009
DOI: 10.1029/2009gl039120
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the Wyrtki Jet observed with surface drifting buoys and satellite altimeter

Abstract: Analyses of up‐to‐date data from satellite‐tracked surface drifters indicate that the Wyrtki Jets (WJ) of the equatorial Indian Ocean (EIO) are developed firstly in the central EIO between 75°E and 80°E and then propagate westward along the equator at speeds of about 0.7 m s−1. Climatologically, the fall jet is both stronger and wider than its spring counterpart. This westward propagation phenomenon is supported by altimetry observation. It is suggested that the westward propagation of the jets in the western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 35 publications
4
50
1
1
Order By: Relevance
“…In the Indian Ocean, the optimal correlation location is along the equatorial region where the Wyrki Jet is generated [i.e., Clark and Liu , 1994; Iskandar et al ., ; Qiu et al ., ; Schiller et al ., ; Wijffels and Meyers , ; Wyrtki , ]. Such a coincident is consistent with the field measurements that show that the ITF in the Makassar Strait is strongly influenced by intrusions of semiannual Kelvin waves from the Indian Ocean [ Sprintall et al ., ].…”
Section: Optimal Correlationsmentioning
confidence: 71%
“…In the Indian Ocean, the optimal correlation location is along the equatorial region where the Wyrki Jet is generated [i.e., Clark and Liu , 1994; Iskandar et al ., ; Qiu et al ., ; Schiller et al ., ; Wijffels and Meyers , ; Wyrtki , ]. Such a coincident is consistent with the field measurements that show that the ITF in the Makassar Strait is strongly influenced by intrusions of semiannual Kelvin waves from the Indian Ocean [ Sprintall et al ., ].…”
Section: Optimal Correlationsmentioning
confidence: 71%
“…In addition to semiannual, the IL also exhibits well-defined annual variability, deepening during austral winter (June-September) and shoaling in summer (January-April) months. The equatorial convergence of water in response to annual component of zonal westerlies in winter months (June-September), and vice-versa in summer is primarily responsible for this annual variation [Qu and Meyers, 2005;Qiu et al, 2009]. [11] In contrast to the western Indian Ocean, where the IL and ML seasonal variations are almost identical (Figures 1b and 1c), the ML depth is significantly shallower than the IL all year round in the east, because of local rainfall and a freshwater input from the Bay of Bengal and the Indonesian Throughflow [Sengupta et al, 2006].…”
Section: Seasonal Cyclementioning
confidence: 99%
“…Nagura and McPhaden [2008] found from four yearlong observational record that interannual variability in zonal momentum balance in the central equatorial Indian Ocean can largely be interpreted in terms of linear dynamics. Qiu et al [2009] reported the westward phase propagation in the equatorial currents, which they attributed to the westward phase propagation of zonal winds in the western equatorial Indian Ocean. Nagura and McPhaden [2010a] studied this westward propagation in detail using a linear continuous stratified model, and interpreted the westward propagation as a result of a superposition of Rossby waves on a wind forced jet.…”
Section: Introductionmentioning
confidence: 99%